Detailed study of quantum path interferences in high harmonic generation driven by chirped laser pulses. (8th December 2021) - Csizmadia, Tamás; Gulyás Oldal, Lénárd; Ye, Peng; Majorosi, Szilárd; Tzallas, Paraskevas; Sansone, Giuseppe; Tosa, Valer; Varjú, Katalin; Major, Balázs; Kahaly, Subhendu
Abstract: We investigate the electron quantum path interference (QPI) effects during high harmonic generation in atomic gas medium driven by ultrashort chirped laser pulses. To achieve that, we identify and vary the different experimentally relevant control parameters of such a driving laser pulse influencing the high harmonic spectra. Specifically, the impact of the pulse duration (from the few-cycle to the multi-cycle domain), peak intensity and instantaneous frequency is studied in a self-consistent manner. Simulations involving macroscopic propagation effects are also considered. The study aims to reveal the microscopic background behind a variety of interference patterns capturing important information both about the fundamental laser field and the generation process itself. The results provide guidance towards experiments with chirp control as a tool to unravel, explain and utilize the rich and complex interplay between QPIs including the tuning of the periodicity of the intensity dependent oscillation of the harmonic signal, and the curvature of spectrally resolved Maker fringes.